Knowledge and attitude of graduates ' nursing technical school toward bio-psychosocial needs of elderly - Dalia Hussein Seif; Inas Helmy Elshair; Nagat Said Habib (Cairo : Dalia Hussein Seif, 2021)
Background: graduates nurses are increasingly in demand for improving and providing life services among the elderly. Having substantial knowledge and positive attitude towards ageing will be a key step towards better care giving. Aim: This study aimed to assess knowledge and attitude of graduates' technical nursing school toward bio-psychosocial needs of elderly. Subjects and Methods: A descriptive research design was used via demographic self administered questionnaire and Kogan Attitude toward Older People Scale (KAOPS), it was completed by 200 graduates technical nurses from Cairo university hospital and El Qasr El Ainy new educational hospital using a convenient sampling technique. Results: Forty eight percent of the study subjects had average level of total knowledge score. In addition, 40% had neutral level of total attitude score. A highly statistically significant positive relation was found between the study subjects' total level of knowledge and their total level of attitude, p=0.000 and X2 =31.648. In addition, statistically significant positive relations were found between total knowledge score & total attitude score and the study subjects' age, previous experience, having elderly person within family and prefer working in geriatric services. Conclusion: almost half of the study subjects had average level of total knowledge and more than third of them had neutral attitude toward needs of elderly. Recommendations: A specific training program is needed, in order to give a chance for graduates' nurses to improve their knowledge and enhance their attitude toward Bio-psychosocial needs of elderly
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Community Health Nursing
Issued also as CD
Keywords: Attitude; Graduates' Nursing; Knowledge